Educação e masculinidade na produção jornalística e literária de Bernardo Guimarães (1852-18823) - Matheus da Cruz e Zica (2008)
This dissertation approaches the literary and journalistic production (1852-1883) of Bernardo Guimarães, seeking to elucidate how the better understanding of such practices can lead us to a wider comprehension of the education in 18th century. We have realized, in this research, that the appeal for the orallity, on the part of Guimarães, which is seen in a negative way on the part of the classic interpreters, would come just to reveal his conscience about his production, about the most recurring form of reading in his time, namely the practice of reading aloud, spread by the habit of reading newspaper in that way, and about the population to who the author wished, with this procedure, to reach. We also have seen that the journalistic and literary practices have already other points in common in 19th century. By showing how close those two practices are, in relation to the reader whom they are addressed to, to the forms of writing, and to the form of placing themselves before the public, our work ended up exposing in them both concern in with an educational position. We reason out, with these verifications, that the coincidences, even among the content transmitted by journalism and literature, in Bernardo Guimarães, would indicate an educational pretension in the author´s own literary writings. Moreover, we observed that in these two branch of his written production it is possible to identify an educational concern also in relation to the politic discussions about national identity occurred in that period. In such case, we discussed that Bernardo Guimarães have used metaphors through which the challenges faced by the main characters of his stories would represent the challenges to be faced by the very nation, since there were coincidences between the main characters features and the ones of the nation in that period: youths, dwellers of the back country, and mixed races. Besides, this dissertation will also bring analysis of some questions about the representations of the masculinity of the 19th century, from the literary production of Bernardo Guimarães. The author seemingly wished to explain by his writings the masculine logic of collecting women.